Estudos eletroquímicos das ligas biocompatíveis Ti-50Zr (at.%) e Ti-13Nb-13Zr (m/m) - Oliveira, Nilson Tadeu Camarinho de (2004)
Studies on the anodic growth of the oxides that passivate the biocompatible alloys Ti-50Zr (at.%) and Ti-13Nb-13Zr (m/m), on the electrochemical/electrical parameters and the morphology, composition and structure of these oxides were carried out in this work. The oxides were grown by both the potentiodynamic and the galvanostatic routes, in different electrolytes at room temperature; their electrochemical stability was investigated in electrolytes that simulate the physiological medium. Based on the analyses carried out, it was concluded that the Ti-13Nb-13Zr alloy presented better protection against corrosion than the Ti-50Zr alloy and that the heat treatment of the alloy did not significantly influence the analysed electrochemical parameters. It was also shown that the pre-passivation of these metals in an inert electrolyte confers the oxides greater stability when exposed to chloride-containing media. The studies by electrochemical impedance spectroscopy indicated that the oxide films of both alloys present an electrical response of the R(RQ) type and that the resistance of the anodic oxide films increases with their thickness. Finally, based on results obtained by photocurrent spectroscopy (PCS), X-ray photoelectron spectroscopy (XPS) and X-ray diffractometry (XRD), it was verified that the anodic oxides grown on the alloys are formed by oxides of all the alloying elements, but with an enrichment in Ti in the oxide external layers.